Profile of Mathematical Connection Ability Viewed from The Cognitive Styles of Field Independent and Field Dependent Students - Dadah Nurhayati; Agus Jaenudin; Neneng Tita Rosita (MASI Mandiri Edukasi, 2026)
This study aims to describe the profile of students’ mathematical connection ability, as viewed through the cognitive styles of Field Independent (FI) and Field Dependent (FD), in the topic of Social Arithmetic. The research subjects were 32 students of class VIII-B at SMPN 1 Cimalaka. Cognitive style classification was conducted using the Group Embedded Figure Test (GEFT), after which students completed a mathematical connection ability test comprising three contextual problems that required integrating concepts (direct proportion, percentage, currency exchange, and profit/loss) and connecting mathematics to real-life contexts. Data were analyzed using a descriptive qualitative approach through data reduction, data display, and conclusion drawing. The results showed that the cognitive style composition consisted of 14 FI students (43.75%) and 18 FD students (56.25%). Mastery based on the minimum competency criterion (KKTP 75) indicated that the FI group achieved a higher level of mastery (12 students) compared to the FD group (1 student), while non-mastery was predominantly found in the FD group (17 students). These findings indicate that FI students tend to be more consistent in integrating concepts to produce complete solutions and final decisions. In contrast, FD students require more supportive structures (tables, step-by-step procedures, and guiding questions) for mathematical connections to be fully developed.